Analysis of Tooth Profile Characteristics and Meshing Characteristics of Double Cycloid Needle Tooth Transmission - Lu Xinhao; Bai Guozhen; Cui Jiankun; Zhang Deqi; Ding Jiale (Jixie chuandong)
In order to solve the problems of the traditional output structure of the cycloid pinion transmission, such as easy damage and complex structure, a new type of cycloid pinion gear is proposed by applying the internal and external cycloid tooth profile to the field of NN-type less differential planetary gear transmission, and the analysis of its tooth profile characteristics and meshing characteristics is carried out. The equations of the tooth profile equation and pressure angle of the cycloid are derived, and the influence of the tooth profile parameters on the pressure angle is analyzed to lay the foundation for the application of this new transmission system. The parameter equations of the inner and outer cycloid gears under different tooth profile modification methods are derived, and the simulation analysis is carried out using Matlab software to solve the meshing gap problem due to a series of reasons such as lubrication mucosa and manufacturing errors. Finally, the mechanical characteristics of the double cycloid needle gear transmission are analyzed, which provides a theoretical basis for the subsequent design of the reducer and finite element analysis. This study has significance and engineering use value for the development of new transmission methods.